2011
DOI: 10.1007/s00247-011-2032-4
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the New Orleans Criteria (NOC), the Canadian CT Head Rule (CCHR) and the National Emergency X-Radiography Utilization Study II (NEXUS II) for CT scanning in pediatric patients with minor head injury in a non-trauma center

Abstract: The number of cranial CT scans conducted in our pediatric cohort with head trauma would have been reduced had any of the three clinical decision aids been applied. Therefore, we recommend that further validation and adoption of pediatric head CT decision aids in non-trauma centers be considered to ultimately increase patient safety while reducing medical expense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 18 publications
1
24
0
3
Order By: Relevance
“…Schachar et al (32) found that use of clinical decision aids resulted in a 10.9% reduction in CT scans in pediatric patients with head trauma.…”
Section: Discussionmentioning
confidence: 98%
“…Schachar et al (32) found that use of clinical decision aids resulted in a 10.9% reduction in CT scans in pediatric patients with head trauma.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that relatively large populations are needed to fairly compare rule application in cases in which intracranial lesions with clinical impact are so uncommon. Although many of the clinical rules discussed earlier were derived with all age groups in mind, distinct clinical decision rules have also been proposed to guide CT scan use in mild TBI for children [64][65][66][67][68][69][70][71] and for the elderly. 72 CONCLUSION Clinical prediction and decision rules are able to integrate more data points than a clinician can handle and are more consistent.…”
Section: Neurosurgical Clinical Prediction and Decision Rulesmentioning
confidence: 99%
“…34 Other retrospective studies have found similarly high sensitivity and NPV with variable specificity, including the National Institute for Health and Care Excellence guidelines; the Children's Head Injury Algorithm for the Prediction of Important Clinical Events; and the Canadian Assessment of Tomography for Childhood Head Injury. [37][38][39][40] In a patient of any age with a moderate/severe brain injury or a minor head injury with altered mental status or signs of a basilar skull fracture, either a non-contrast head CT or magnetic resonance imaging (MRI) (if readily available) is appropriate to assess for injury. Children with seemingly minor head injury accompanied by altered mental status and/or skull fracture have a 4% increased risk of traumatic brain injury; these children are considered high risk.…”
Section: Head Traumamentioning
confidence: 99%